Rosmarinic acid treatment protects against lethal H1N1 virus-mediated inflammation and lung injury by promoting activation of the h-PGDS-PGD2-HO-1 signal axis - Beixian Zhou; Linxin Wang; Sushan Yang; Yueyun Liang; Yuehan Zhang; Xiping Pan; Jing Li (BMC, 2023)
Abstract Background Rosmarinic acid (RosA) is a natural phenolic compound that possesses a wide-range of pharmacological properties. However, the effects of RosA on influenza A virus-mediated acute lung injury remain unknown. In this study, we aimed to explore whether RosA could protect against H1N1 virus-mediated lung injury and elucidate the underlying mechanisms. Methods Mice were intragastrically administered with RosA for 2 days before intranasal inoculation of the H1N1 virus (5LD50) for the establishment of an acute lung injury model. At day 7 post-infection (p.i.), gross anatomic lung pathology, lung histopathologic, and lung index (lung weight/body weight) were examined. Luminex assay, multiple immunofluorescence and flow cytometry were performed to detect the levels of pro-inflammatory cytokines and apoptosis, respectively. Western blotting and plasmid transfection with hematopoietic-type PGD2 synthase (h-PGDS) overexpression were conducted to elucidate the mechanisms. Results RosA effectively attenuated H1N1 virus-triggered deterioration of gross anatomical morphology, worsened lung histopathology, and elevated lung index. Excessive pro-inflammatory reactions, aberrant alveolar epithelial cell apoptosis, and cytotoxic CD8+ T lung recruitment in the lung tissues induced by H1N1 virus infection were observed to be reduced by RosA treatment. In vitro experiments demonstrated that RosA treatment dose-dependently suppressed the increased levels of pro-inflammatory mediators and apoptosis through inhibition of nuclear factor kappa B (NF-κB) and P38 MAPK signaling pathways in H1N1 virus-infected A549 cells, which was accompanied by promoting activation of the h-PGDS-PGD2-HO-1 signal axis. Furthermore, we strikingly found that h-PGDS inhibition significantly abrogated the inhibitory effects of RosA on H1N1 virus-mediated activation of NF-κB and P38 MAPK signaling pathways, resulting in diminishing the suppressive effects on the increased levels of pro-inflammatory cytokines and chemokines as well as apoptosis. Finally, suppressing h-PGDS prominently abolished the protective effects of RosA on H1N1 virus-mediated severe pneumonia and lung injury. Conclusions Taken together, our study demonstrates that RosA is a promising compound to alleviate H1N1 virus-induced severe lung injury through prompting the h-PGDS-PGD2-HO-1 signal axis.